Platelet Membrane Glycoproteins and the Interaction between Bovine Factor VIII Related Protein and Human Platelets - Solum, Nils Olav; Hagen, Inger; Gjemdal, Torbjørn (Thrombosis and Haemostasis, 1977)
The “GP I fraction” seen on polyacrylamide gel electrophoresis of reduced samples of whole normal platelets contains three glycopolypeptides corresponding to the integral membrane protein GP I (GP Ia), the easily solubilized membrane protein GPS (GP Ib, glycocalicin) and a granule-located glycoprotein.Freezing and thawing of platelets in tris-buffered saline leads to a lysis of platelets and platelet granules with the result that both GPS and the granule glycoprotein is found in the soluble fraction. The two glycoproteins can be separated by SDS polyacrylamide gel electrophoresis both in reduced and unreduced samples when urea and EDTA is incorporated into the gels. This permitted electrophoretic studies of GPS using the granule glycoprotein as a control and marker substance.A working hypothesis stating that the presence of GPS on the platelet surface is a prerequisite to the agglutination of human platelets with bovine factor VIII related protein, has been investigated. The hypothesis was supported by the observation that storage of platelets in tris-buffered saline at 4° C led to the elution of GPS and loss of agglutination, as was also the case when platelets were frozen and thawed in tris-buffered saline, or preincubated in 3 M KCl and resuspended in either tris-buffered saline or the EDTA-containing medium A. GPS was not, or only slightly, solubilized when platelets were frozen and thawed in the EDTA-containing medium and the resulting platelet ghosts still agglutinated.Platelets from 1 patient of the Bernard-Soulier type did not agglutinate with the bovine factor VIII-related protein, nor did the platelets contain GPS. An improved technique for the isolation of such platelets is described.